2007
DOI: 10.1007/s10565-007-9051-9
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to 9-cis retinoic acid induces penis and vas deferens development in the female rock shell, Thais clavigera

Abstract: To clarify how tributyltin (TBT) and triphenyltin (TPT) interact with the retinoid X receptor (RXR) to induce growth of male sex organs in female gastropods, we treated female rock shells (Thais clavigera) with three different concentrations (0.1, 1, or 5 microg/g wet wt) of 9-cis-retinoic acid (9CRA) or with a single concentration (1 microg/g wet wt) of TBT, TPT, or fetal bovine serum (as a control). The effects of each treatment were measured as the incidence of imposex, the length of the penis-like structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 51 publications
0
17
0
1
Order By: Relevance
“…Cloning of the RXR homologue from the gastropod rock shell (Thais clavigera) reveals that the ligand-binding domain of rock shell RXR is very similar to human RXR and also binds strongly to TBT [Nishikawa et al 2004;Nishikawa 2006]. It was discovered that activation of RXR through injections of RA into female rock shells induces imposex [Horiguchi et al 2008]. These results suggest that RXR plays a critical role in the development of imposex and is important in the induction, differentiation, and growth of male reproductive organs in female gastropods.…”
Section: Marine Mollusks and Chemical Induced Imposexmentioning
confidence: 99%
“…Cloning of the RXR homologue from the gastropod rock shell (Thais clavigera) reveals that the ligand-binding domain of rock shell RXR is very similar to human RXR and also binds strongly to TBT [Nishikawa et al 2004;Nishikawa 2006]. It was discovered that activation of RXR through injections of RA into female rock shells induces imposex [Horiguchi et al 2008]. These results suggest that RXR plays a critical role in the development of imposex and is important in the induction, differentiation, and growth of male reproductive organs in female gastropods.…”
Section: Marine Mollusks and Chemical Induced Imposexmentioning
confidence: 99%
“…Although oestrogenic effects predominate the ED literature on fish, a small number of masculinization events have been reported in several FW species (mosquitofish, killifish and catfish) in conjunction with exposure to pulp mill effluent (possibly due to androstenedione from bacterial degradation of plant sterols) and also from inputs of androgenic anabolic steroids from intensive cattle farming (Howell, 1999). Downstream, estuarine and coastal fauna could be vulnerable to these and other androgenic EDC (Alvarez-Munoz et al ., 2015), given that the androgen receptor (AR) in some marine species is known to bind contaminants such as organochlorines, albeit weakly, which may subsequently impair the gamete-maturation signalling pathway (Oberdorster & Cheek, 2001).…”
Section: Endocrine Disruption and Reproductive Effects In Aquatic Biotamentioning
confidence: 99%
“…However, the scientific debate continues on the mechanisms by which organotins induce imposex in gastropods because, as noted by Horiguchi et al (2008) and Horiguchi (2009), each of these hypotheses is insufficient to explain the phenomenon. Nishikawa et al (2004) found that T. clavigera has a retinoid X receptor (RXR) that is similar to those in humans and other vertebrates as well as to those in other invertebrates, such as ascidians, insects, pulmonates, jellyfish, and sponges (Bouton et al 2005;Devine et al 2002;Freebern et al 1999;Heyman et al 1992;Kamimura et al 2000;Kostrouch et al 1998;Mangelsdorf and Evans 1995;Mangelsdorf et al 1992;Wiens et al 2003).…”
Section: Introductionmentioning
confidence: 99%